Genetic Analysis of Mu and Kappa Opioid Receptor and COMT Enzyme in Cancer Pain Tunisian Patients Under Opioid Treatment - Imen CHATTI; Jean-Baptiste WOILLARD; Amira MILI; Isabelle CREVEAUX; Ilhem BEN CHARFEDDINE; Jihène FEKI; Sarah LANGLAIS; Leila BEN FATMA; Ali SAAD; Moez GRIBAA; Frédéric LIBERT (Tehran University of Medical Sciences, 2017)
Background: Pain and its opioid treatments are complex measurable traits. Responses to morphine in terms of pain control is likely to be determined by many factors, including the underlying pain sensitivity of the patient, along with nature and extent of the painful process, concomitant medications, genetic and other clinical and environmental factors. This study investigated genetic polymorphisms implicated in the inter-individual pain response variability to opioid treatment in the Tunisian population. Methods: This prospective association study investigated seven variations in the OPRM1, OPRK1 and COMT gene, which encode Mu and KAPPA opioid receptors, and Catechol-O-methyltransferase enzyme respectively, in a cohort of 129 Tunisian cancer pain patients under oral morphine treatment. Genotyping was performed by simple probe probes on Light Cyler for rs17174629, rs1799972, rs1799971, rs1051659, rs1051660 and rs4680 and by PCR assay for the indel in the promoter region of OPRK1 (rs35566036). A statistical associations study between dose (continuous), dose escalation (yes/no) and SNP or haplotypes were investigated using linear multiple regressions and logistic regressions respectively adjusted on metastases and pain covariates in the R software. Results: We detected significant association of the rs1051660 adjusted on metastasis and pain (P=0.02), no other association has been detected between the 7 polymorphisms screened and the dose of morphine needed for pain relief. Conclusion: This can be explained by the strong genetic heterogeneity in the cosmopolitan areas where our patients were recruited for this study, compared to more homegenous population recruited in other studies.